2001
DOI: 10.1007/s100380170115
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DMC1, a novel gene in the TOC region on 17q25.1 that shows loss of expression in multiple human cancers

Abstract: Frequent allelic losses within chromosomal band 17q25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…obtained. A polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) analysis for each exon was carried out as described previously (Harada et al 2001) by using the PCR primer sets shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…obtained. A polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) analysis for each exon was carried out as described previously (Harada et al 2001) by using the PCR primer sets shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…To search for germline mutation in the NF2 gene, we amplified all seventeen exons of the gene in genomic DNA from blood of patients B and C as well as cancerfree volunteers (Harada et al, 2001) using the primers described by Jacoby et al (1994) (Table 2). Direct sequencing of the entire coding region was carried out as previously described (Iwasaki et al, 2001).…”
Section: Patientmentioning
confidence: 99%
“…PCR amplification of the polymorphism at the GSBS locus was carried out using a condition described previously Harada et al 2001); primer sequences used are as follows: forward primer: 5¢-TGCGTGGCTTCAAATGATTA C-3¢; reverse primer: 5¢-ACAGGTCCAG TCCTGCTGAC-3¢. The surrounding sequence of the amino acid-substituting SNP in the GSBS gene, i.e., polymorphic nucleotides T/C substitution at the )1323 position as well as primer sequences and experimental conditions were obtained from published reports (Haga et al 2002).…”
Section: Genotyping For Single Nucleotide Polymorphism (Snp)mentioning
confidence: 99%